Lifestyle, Nutritional and Biochemical Factors Associated with Acute Myocardial Infarction Among Patients at Shahid Mostafa Khomeini Hospital , Ilam Iran - Yary, Teymoor (2011)
Myocardial infarction (MI) seriously threatens public health all over the world, especially in developing countries. Epidemiological studies have documented that risk factors, including smoking, diet, and a person’s biochemical profile are responsible for the development of acute myocardial infarction (AMI). This epidemic disproportionately affects ethnic populations and has racial correlation. According to the Ministry of Health in Iran, each day 300 people die of AMI, affecting women over 50 years of age and men over 32 years of age. Changes in lifestyle, the rapid urbanization, and desperate socio-economic status have been correlated with the occurrence of AMI. This case-control study was conducted on 120 cases of AMI and 120 control patients. Clinical criteria, electrocardiographic criteria, and biochemical markers defined an AMI. Control cases comprised 120 individuals who received routine health checkups at the same hospital. Cases and controls were matched by age and sex. Standard questionnaire and physiological measures were used to obtain data. The case and control groups were compared using parametric and nonparametric test, as required. For final analyses, a binary unconditional logistic regression analysis was conducted to identify independent predictors for AMI in the case-control model. In the binary logistic regression analysis, the risk factors for developing AMI were evaluated using independent variables recognized by the American Heart Association and documented in the literature review. These risk factors have both epidemiological and clinical importance. The result derived revealed that hypertension (odd ratio (OR) =3.9, 95% intervals (CI) 1.4-10.9); family history of coronary heart disease (OR=6.8, 95% CI 2.4-19.6); physical inactivity (O=2.9,95% CI 1.1-7.4) and fasting blood sugar (FBS) (OR=4.3, 95% CI 1.4-13.2), and for anthropometric parameters, only waist-hip ratio (WHR)(OR=2.6, 95% CI1.2-5.6) were risk factors for AMI. Among nutrients variables, high saturated fat (OR=2.7, 95% CI 1.2-6.0) was an independent risk factor for AMI. Low consumption of total dietary fiber (TDF) (OR=8.3, 95% CI 2.0-34.6) was also a significant independent risk factor for AMI. IN conclusion, the present study found several risk factors for AMI in this sample. It is recommended that appropriate interventions and systematic health education programs be implemented for the Ilamian people to reduce the incidence and mortality rate o AMI.